2011
DOI: 10.2169/internalmedicine.50.5280
|View full text |Cite
|
Sign up to set email alerts
|

Difference of Clinical Course after Catheter Ablation of Atrioventricular Nodal Reentrant Tachycardia between Younger and Older Patients: Atrial Vulnerability Predicts New Onset of Atrial Fibrillation

Abstract: Background The aim of this study was to compare the long-term procedural outcomes, the stability of atrioventricular conduction, and the new onset of atrial fibrillation (AF), after ablation of atrioventricular nodal reentrant tachycardia (AVNRT). Methods and ResultsConsecutive patients with AVNRT (n=109), who underwent slow-pathway ablation, were divided into two groups based on the median age of the studied patients: the younger group aged <55 years and the older group aged !55 years. During a mean follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…History of AF and increased atrial vulnerability were moreover found to be risk factors of later AF. Arimoto et al [ 21 ] also reported that physicians should consider regular long-term follow-up of older patients with atrial vulnerability in order to assess the subsequent development of AF. Importantly, in patients without AF history or AF during follow-up in the present series, 17 patients (1.1%) in those aged <70 and 9 (3.4%) in those aged 70 or older experienced a stroke during follow-up ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…History of AF and increased atrial vulnerability were moreover found to be risk factors of later AF. Arimoto et al [ 21 ] also reported that physicians should consider regular long-term follow-up of older patients with atrial vulnerability in order to assess the subsequent development of AF. Importantly, in patients without AF history or AF during follow-up in the present series, 17 patients (1.1%) in those aged <70 and 9 (3.4%) in those aged 70 or older experienced a stroke during follow-up ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial risk of AF has been reported in patients with AVNRT [20][21][22][23][24][25], reaching as high as 12% during a mean 1-year follow-up [22]. In a recent study by Ozcan et al [26] AF was seen in 27% of 1573 patients, and AF was seen in 19.6% of patients before ablation of the SVT and 9.07% after ablation of an SVT aside from AF In a previous study by our group [20] performed in patients recruited in the 1980's and 1990's, we reported that patients with AVNRT had a 5% risk of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Although long-term AVNRT recurrence rate is low, the risk of persistent inappropriate sinus tachycardia [18,19] and atrial fibrillation (AF) or other atrial arrhythmias is increased after AVNRT ablation [20][21][22][23][24][25]. In untreated patients with AVNRT, AF has been shown to occur in as high as 12% of patients within one year of follow-up [22].…”
Section: Introductionmentioning
confidence: 99%